2017
DOI: 10.1177/1687814017695955
|View full text |Cite
|
Sign up to set email alerts
|

Lateral motion of the endless flat belt in a two-pulley belt system

Abstract: An analytical model of the lateral motion of the endless belt in a two-pulley belt system is proposed. This model can be used to forecast the transient and steady lateral motion of the belt when the tilted angle of the steering pulley is timevariant and it is valuable in the design and assessment of belt lateral position controllers. The responses of the belt to variations in the tilted angle of the steering pulley according to a piecewise step function are solved using the delay differential equation solver d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…He also showed that the skew ratio varied with the belt width. Fenglin et al proposed a simulation method that could forecast the transient and steady lateral motion of a belt using the solver dde23 in MATLAB, and the simulation results agreed well with the experimental ones (Fenglin et al, 2017). Furthermore, they proposed a closed-form expression for the lateral velocity of the belt and showed that the velocity increased with an increase in the tilt angle, belt speed, and tension, and decreased with an increase in the radius of the pulley.…”
Section: Introductionmentioning
confidence: 86%
“…He also showed that the skew ratio varied with the belt width. Fenglin et al proposed a simulation method that could forecast the transient and steady lateral motion of a belt using the solver dde23 in MATLAB, and the simulation results agreed well with the experimental ones (Fenglin et al, 2017). Furthermore, they proposed a closed-form expression for the lateral velocity of the belt and showed that the velocity increased with an increase in the tilt angle, belt speed, and tension, and decreased with an increase in the radius of the pulley.…”
Section: Introductionmentioning
confidence: 86%
“…The tensioner consists of a base (1), a torsional spring (2), a tensioner arm (3), and a friction disk (6), and so on. The description for each component and the mechanical fit among components of tensioner are shown in Tables 1 and 2. As shown in Figure 1(b), owing to the rotation of tensioner arm (3), a counter torque is generated by the torsional spring (2). Two types of friction torques are generated: the friction torque (M f1 ) between the top surface of bushing (4) and friction disk (6), and the friction torque (M f2 ) between the cylindrical contact surfaces of the bushing (4) and the pivot shaft (5).…”
Section: Structure Of Tensioner and Friction Torquesmentioning
confidence: 99%
“…As shown in Figure 1(b), owing to the rotation of tensioner arm (3), a counter torque is generated by the torsional spring (2). Two types of friction torques are generated: the friction torque (M f1 ) between the top surface of bushing (4) and friction disk (6), and the friction torque (M f2 ) between the cylindrical contact surfaces of the bushing (4) and the pivot shaft (5).…”
Section: Structure Of Tensioner and Friction Torquesmentioning
confidence: 99%
See 2 more Smart Citations